Dilemas Related to Potential Changes in the Taxation of Farms - Podstawka, Marian Grzegorz (Management and Administration Journal, 2020)
Abstract: Polish farms are burdened with the following taxes: agricultural tax, forestry tax, property tax, motor vehicle tax, VAT, and excise tax.The research showed that small farms suffered losses in the years 2014-2018. However, income made by small farms (income of EUR 8,000 to 25,000) was burdened with all taxes ranging from 29.9% in 2014 to 67.05% in total. In 2018, middle-sized farms with income between EUR 50,000 and EUR100,000 had a share of all taxes in their income of about 4-6%. Very large farms (>EUR 500,000 of income) had a symbolic tax burden of ca. 1%.In the case of the tax burden on farms’ revenues, very small and small farms were in the worst situation, similarly as before. They recorded ca. 2.7% of taxes in their revenues. The medium-sized farms had a burden of ca. 1% of their revenues with all taxes. By contrast, the revenues of very large farms were burdened with symbolic taxes in the amount of ca. 0.2%. In this situation, while maintaining the current tax burden borne by farms, it should be remembered that the income tax rate and the revenue tax rate cannot exceed 5% and ca. 1%, respectively.